Role of Autonomic Nervous System and Orexinergic System on Adipose Tissue - Messina, Giovanni; Valenzano, Anna; Moscatelli, Fiorenzo; Salerno, Monica; Lonigro, Antonio; Esposito, Teresa; Monda, Vincenzo; Corso, Gaetano; Messina, Antonietta; Viggiano, Andrea; Triggiani, Antonio I.; Chieffi, Sergio; et al. (Frontiers in Physiology, 2017)
Adipose tissue, defined as white adipose tissue (WAT) and brown adipose tissue (BAT), is a biological caloric reservoir that expands in response to over-nutrition and releases lipids in response to energy deficit. The WAT primarily stores energy as triglycerides, whereas BAT dissipates chemical energy as heat. In mammals, the BAT is a key site for heat production and an attractive target to promote weight loss. The autonomic nervous system (ANS) exerts a direct control at the cellular and molecular levels in adiposity. The sympathetic nervous system (SNS) provides a complex homeostatic control to specifically coordinate function and crosstalk of both fat pads, as indicated by the increase of the sympathetic outflow to BAT, in response to cold and high-fat diet, but also by the increase or decrease of the sympathetic outflow to selected WAT depots, in response to different lipolytic requirements of these two conditions. More recently, a role has been attributed to the parasympathetic nervous system (PNS) in modulating both adipose tissue insulin-mediated glucose uptake and fatty free acid (FFA) metabolism in an anabolic way and its endocrine function. The regulation of adipose tissue is unlikely to be limited to the autonomic control, since a number of signaling cytokines and neuropeptides play an important role, as well. In this review we report some experimental evidences about the role played by both the ANS and orexins into different fat pads, related to food intake and energy expenditure, with a special emphasis on body weight status and fat mass (FM) content.